THE MAIN FORMS OF PHYSICAL CULTURE IN HIGHER EDUCATIONAL INSTITUTIONS OF THE MEDICAL PROFILE - Тухтахужаев Ханжарбек Боходирович (American Journals, 2023)
In article relevance and a role of physical culture and sport in higher educational institutions of a medical profile, and the organization of sports and sports club at a medical university, the student's duty concerning physical training in higher education institution is considered.